Ing Ngarsa Sung Tuladha: Empowerment In MSMEs in Bantul Indonesia and Community Learning Center in Malaysia - Kurniawan, Ignatius Soni; Purnamarini, Tri Ratna; Nisa, Ana Fitrotun; Wahidah, Umi; Lada, Suddin Bin (Research Collaboration Community (Rescollacom), 2024)
This research aims to explain of applying Ing Ngarsa Sung Tuladha from Ki Hajar Dewantara’s Trilogy to the leadership of pottery & ceramics crafts SMEs “Dwiyanto Ceramic”, Azka Furniture Bantul SMEs, Rama Putra Motor Bantul SMEs and Community Learning Center (CLC) Ladang Lumadan. This community service method uses direct and remote observation with interview techniques trough the Zoom application. The concept used is the concept of Ing Ngarsa Sung Tuladha to help problems and solusions in leadership to achieve common goals. By conducting socialization and training offline and online. The results of the observation can implement the leadership attitude of Ing Ngarsa Sung Tuladha in pottery & ceramic craft SMEs “Dwiyanto Ceramic”, Azka Furniture Bantul SMEs, Rama Putra Motor Bantul SMEs, and Community Learning Center (CLC) Ladang Lumadan. With this collaboration, it was seen that ineffective leadership methods resulted in solutions with Ing Ngasra Sung Tuladha